PHYSICAL ACTIVITY AND COLORECTAL CANCER - Martina Perše; Anton Cerar (Zdravniški Vestnik, 2009)
Background Colorectal cancer is one of the most frequent cancers in man. Its incidence is increasing in Slovenia as well as in the developing countries. It is believed that between 60 % and 80 % of colorectal cancer in Western countries is attributable to environmental factors. The evidence that physical activity protects against colorectal cancer is convincing, although the evidence is stronger for colon than for rectum. conclusions The present paper summarizes the main recently published data concerning an association between physical activity and colon cancer risk and presents proposed beneficial mechanisms of exercise involved in the prevention of cancer.